Implementasi Sistem Asset Manajemen Sebagai Penunjang Operasional Laboratorium Komputer - Tanty Oktavia (Universitas Multimedia Nusantara, 2014)
Currently most organization have assets to support operational processes. Although a number of organizations tend to use outsourcing and leasing services to organize their assets, but some organization prefer to buy their own and manage their assets with a particular reason. Asset management is not a simple job. It’s very difficult to manage assets without information systems as support media. Integrating asset management into information system can help organization to record and update the status of assets, maintenance and repair of assets, calculate asset depreciation, and asset reallocation among divisions. ABC as part of the computer laboratory at a well known University in Jakarta is currently had many problems to manage their assets. The composition of their assets consists of hardware, software, and other supporting devices. Based on these problems, the research carried out in order to solve the problem. The research perform an analysis of the process in asset management as well as to formulate and implement a model of information system that can support the management of existing assets, so that all data can be integrated and managed with the system. The method for this research is based on analysis and design of object-oriented. The result of this research is an asset management system to support operational process that can be used to control all the assets that exist in the computer laboratory Keywords: asset management, information system, computer laboratory